CASE STUDY OF FUTURE DOCTORS OF PHILOSOPHY DIGITAL COMPETENCE FORMATION - Lutsenko, Galyna (Journal of Information Technologies in Education (ITE), 2025)
The rapid digitalization across various spheres of human activity is reshaping the requirements of educational programs designed to train future Doctors of Philosophy (PhDs). This has sparked active discussions within the scientific community and higher educational institutions about the importance of developing digital competence among future Doctors of Philosophy. This article examines the role and significance of information and digital technologies in research practice, focusing on contemporary approaches to defining the concept of digital competence for future PhDs. It highlights global initiatives, such as those by Vitae and JISC, which provide structured frameworks for describing the professional qualities and digital competencies necessary for researchers in both academic and organizational contexts. Additionally, the article discusses practical experiences in organizing PhDs training through the course "Information and Communication Technologies in Scientific Research". The content of this course is aligned with the competencies and professional qualities required for conducting research, as outlined by these international frameworks. A detailed survey was carried out among future Doctors of Philosophy, and the results are presented, shedding light on their needs regarding digital skills and the course content. The survey also reflects the PhDs' experiences with using digital tools in their research, the challenges they face, and the course’s influence on their development of digital competencies. The findings reveal a strong demand for the enhancement of digital skills across a broad spectrum, including the use of specialized tools, information management services, and digital communication platforms. These insights will be instrumental in further refining the course on the use of digital technologies in scientific research.